Pemanfaatan Diversifikasi Olahan Jagung untuk Meningkatkan Gizi dan Pendapatan Masyarakat Desa Bohulo Kabupaten Gorontalo Utara - Lamadi, Arafik; Suherman, Sutianto Pratama; Nento, Wila Rumina (University of Merdeka Malang, 2021)
Bohulo Village, North Gorontalo District, is mostly agricultural land planted with rice and maize. The abundant maize yields in the area have not been followed by maximum utilization. The problem is, the farmers' ability to sell their crops is limited. Therefore, it is necessary to increase the use of crops, especially corn, into processed products that can increase community income, namely in the form of corn brownies. The purpose of this community empowerment program is technology transfer to increase the economic value of corn. This approach method is a participatory method consisting of site surveys, training and evaluation. This activity shows the enthusiasm of the community, especially the women in Family Welfare Education or PKK, corn farmers, and community leaders in Bohulo Village. Corn that is processed into various kinds of food not only adds attractiveness but also provides opportunities to increase income so that it can improve community welfare. In the future, corn-based food processing can be developed into various products due to the availability of raw materials.DOI:Â https://doi.org/10.26905/abdimas.v6i1.4920Â